A "Grafting to" Approach to Synthesize Low Cytotoxic Poly(aminoamide)‐Dendrimer‐grafted Fe3O4 Magnetic Nanoparticles. Issue 3 (4th July 2016) - Banaei, Masoud; Salami‐Kalajahi, Mehdi
Abstract: Poly(aminoamide) (PAMAM) dendrimer with 3.5 generation was synthesized with ethylenediamine as the primary core and methyl acrylate. Also, Fe3 O4 nanoparticles as magnetic ones were modified by (3‐aminopropyl)triethoxysilane (APTES) to fabricate amine‐functionalized magnetic nanoparticles (Fe3 O4 @APTES). Then, 3.5GD dendrimer was conjugated with Fe3 O4 @APTES to obtain dendrimer‐grafted magnetic nanoparticles (Fe3 O4 @3.5GD). The core‐shell structure of Fe3 O4 @3.5GD nanoparticles was revealed via TEM. Also, progression of each step was studied by FT‐IR, 1 H NMR, CHN elemental analysis, and thermal gravimetric analysis (TGA). Vibrating sample magnetometer (VSM) was used to show that the synthesized nanoparticles keep their superparamagetic properties after synthesis process. Finally, in vitro cellular cytotoxicity was applied to evaluate the biocompatibility of synthesized structures and investigate the cytotoxic effect of grafted dendrimer using HeLa cells. As a resultS, about 20 wt. % of dendrimer grafting was obtained and good correlation was observed with VSM results. Also, 3.5GD dendrimer showed low cytotoxicity to HeLa cells while after dendrimer grafting, toxicity of Fe3 O4 @3.5GD slightly increased.